Celebrating More Than a Century of Research on Antibodies: Affirmation Through Negation via Complex Formation - Neil S. Greenspan (Case Western Reserve University, 2017)
In this brief commentary, I highlight the remarkable properties of antibodies (also known as immunoglobulins) revealed by more than 100 years of biomedical research. Since antibodies can be elicited through one or another means against almost any molecule or macromolecule, the universe of antibodies represents a sort of molecular mirror for the universe of molecules that make life possible. Consequently, as recounted below, antibodies play a role in almost every aspect of medicine and biomedical research.